Negative correlation between extent of physeal ablation after percutaneous permanent physiodesis and postoperative growth. (August 2013) - Gunderson, Ragnhild B; Horn, Joachim; Kibsgård, Thomas; Kristiansen, Leif Pål; Pripp, Are Hugo; Steen, Harald
<x xml:space="preserve">Abstract</x> Background and purpose Percutaneous physiodesis in the knee region is a well-established method for treating leg-length inequality. Longitudinal growth in the physis is believed to stop almost immediately after the operation. The extent of physis ablation required has never been investigated by any kind of tomography in humans. Using radiostereometric analysis (RSA), we determined when definite growth arrest occurred after surgery. We also studied the correlation between the extent of physis ablation and postoperative growth. Finally, we assessed any bone bridging across the physis. Methods 6, 12, and 30 weeks after surgery, we used RSA to measure longitudinal growth in 27 patients (37 physes) with a mean age of 13 years. CT scanning of the knee region was performed 12 weeks after surgery to measure the percentage of the ablated physis and to determine the distribution of bone bridges across the physis. Results RSA showed that growth rate was reduced to less than half of the expected rate after 6 weeks. During the next 6 weeks, the growth ceased completely. CT scans revealed a large variation in the extent of ablated physes (17–69%). In the ablated areas, tissues of various densities were mixed with mature bone. Bridges were found both laterally and medially across the physes in all of the patients. There was a negative correlation between the extent of ablation and total postoperative growth (rho = –0.37, p = 0.03). Interpretation Growth across the physis is effectively stopped by percutaneous physiodesis. RSA is well-suited for observation of this phenomenon. Volume CT scanning can be used to detect bone bridges that cross the physis and to calculate the extent of physis ablation.